HIPERTIROIDI SUBKLINIK DI DAERAH 'REPLETE' ENDEMIS DEFISIENSI IODIUM - Basuki Budiman; Dhuto Widagdo (Persagi, 2007)
ABSTRACT Background. The evaluation of national program of iodine deficiency disorder (IDD) control in Indonesia revealed that people consumed excess of as measured by urine iodine concentration. The effect of excessive iodine consumption on hemotological features including the development of subclinical hypothyroidism has not been reported in scientific journals yet. Objective. This study aimed toevaluate the correlation of the excessive iodine consumption and hematological features of child bearing age mothers especially in replete iodine deficiency area. Design. Three districts of which formally known as endemic iodine deficiency areas were identified. A total 239 chlid bearing age mothers 17 to 35 years old with strictly inclution participated in this studies. Blood spicemen of eligible participants as much as 2-3 mL was drawn. Thyrotropin hormone (TSH) and free thyroxine (fT4) were performed using third generation of TSH assay (known as sensitive TSH assay) from ILSI certified labolatory. Casual urine sample also collected from school age children (6-12 years of age) as many as 40 samples in each subdistrict to confirm the endemicity of iodine deficiency area based on urine iodine concentration. For analysis purposed, sub-clinical hypothyroidism defined as serum TSH concentration less than 0.4 mU/L. Result. The study found proportion of excess iodine consumption totally was 22.5 percent and varied among three studied area. Participants who developed overt hyperthyroidism found 1.7 percent and sub-clinical hyperthyroidism as much as 9.4 percent. Amongst the three districts, two districts very high in proportion of sub clinical hyperthyroidism.Conclution. Iodine consumption was excessed and lead to adverse effects. Studies on the amount of salt consumption, the humidity, and the length of salt preservatioan at household every area urgently need to do. [Penel Gizi Makan 2007, 30(1): 13-24] Keywords : excess in iodium consumption, TSH, fT4, sub-clinical hypothyroidism, replete endemic deficiency area